Cold-induced dishabituation in rodents exposed to recurrent hypoglycaemia - Vickneson, Keeran (Diabetologia, 2021)
AIMS/HYPOTHESIS: Recurrent hypoglycaemia in people with diabetes leads to progressive suppression of counterregulatory hormonal responses to subsequent hypoglycaemia. Recently it has been proposed that the mechanism underpinning this is a form of adaptive memory referred to as habituation. To test this hypothesis, we use two different durations of cold exposure to examine whether rodents exposed to recurrent hypoglycaemia exhibit two characteristic features of habituation, namely stimulus generalisation and dishabituation. METHODS: In the first study (stimulus generalisation study), hyperinsulinaemic–hypoglycaemic (2.8 mmol/l) glucose clamps were performed in non-diabetic rodents exposed to prior moderate-duration cold (4°C for 3 h) or control conditions. In the second study (dishabituation study), rodents exposed to prior recurrent hypoglycaemia or saline (154 mmol/l NaCl) injections over 4 weeks underwent a longer-duration cold (4°C for 4.5 h) exposure followed 24 h later by a hyperinsulinaemic–hypoglycaemic (2.8 mmol/l) glucose clamp. Output measures were counterregulatory hormone responses during experimental hypoglycaemia. RESULTS: Moderate-duration cold exposure blunted the adrenaline (epinephrine) response (15,266 ± 1920 vs 7981 ± 1258 pmol/l, Control vs Cold; p < 0.05) to next day hypoglycaemia in healthy non-diabetic rodents. In contrast, the suppressed adrenaline response (Control 5912 ± 1417 vs recurrent hypoglycaemia 1836 ± 736 pmol/l; p < 0.05) that is associated with recurrent hypoglycaemia was restored following longer-duration cold exposure (recurrent hypoglycaemia + Cold 4756 ± 826 pmol/l; not significant vs Control). CONCLUSIONS/INTERPRETATION: Non-diabetic rodents exhibit two cardinal features of habituation, namely stimulus generalisation and dishabituation. These findings provide further support for the hypothesis that suppressed counterregulatory responses following exposure to recurrent hypoglycaemia in diabetes result from habituation. GRAPHICAL ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains unedited but peer-reviewed supplementary material available at 10.1007/s00125-021-05425-3.